Understanding Motor Vehicle Taxpayer Compliance: Determinants and the Moderating Role of Tax Socialization Program - Safrida, Lili; Dzikri , Muhammad; Yuliastina, Mellani (Basic and Applied Accounting Research Journal, 2025)
Tax revenue is a major component of national income, essential for funding development and improving public welfare. However, compliance with tax obligations, especially motor vehicle taxes, is often suboptimal. Purpose: This study investigates the determinants of motor vehicle taxpayer compliance—specifically taxpayer awareness, tax knowledge, public service accountability, and tax sanctions—and examines the moderating role of tax socialization programs. Methods: The research was conducted at the Banjarmasin II Samsat Office using a quantitative approach. Data were analyzed using multiple linear regression to test the direct effects of the independent variables on compliance, and moderated regression analysis to evaluate the moderating effect of tax socialization. Results: The results indicate that taxpayer awareness, tax knowledge, public service accountability, and tax sanctions have a significant direct effect on tax compliance. However, tax socialization does not moderate the influence of awareness, knowledge, or sanctions. Notably, tax socialization significantly moderates the effect of public service accountability on taxpayer compliance. Conclusion:Both internal and external factors influence taxpayer behavior. Tax socialization is particularly effective when paired with improvements in public service accountability. These findings offer practical insights for tax authorities aiming to enhance compliance through targeted outreach and service improvements.